2018
DOI: 10.1371/journal.pone.0197077
|View full text |Cite
|
Sign up to set email alerts
|

Keeping up with sea-level rise: Carbonate production rates in Palau and Yap, western Pacific Ocean

Abstract: Coral reefs protect islands from tropical storm waves and provide goods and services for millions of islanders worldwide. Yet it is unknown how coral reefs in general, and carbonate production in particular, will respond to sea-level rise and thermal stress associated with climate change. This study compared the reef-building capacity of different shallow-water habitats at twenty-four sites on each of two islands, Palau and Yap, in the western Pacific Ocean. We were particularly interested in estimating the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 55 publications
3
31
0
Order By: Relevance
“…3–4 mm/year (Hubbard, ) and a little below this in the Indo‐Pacific region (Dullo, ). Whilst some high coral cover sites may sustain vertical accretion rates sufficient to match near‐future sea‐level rise (van Woesik & Cacciapaglia, ), the critical point is that many contemporary coral reefs are now defined by vertical accretion rates that will be insufficient to keep pace with sea‐level rise. Indeed, recent assessments of reef accretion potential at sites around the tropical western Atlantic and Indian Ocean regions suggest that accretion rates presently average only 1.8 mm/year and 2.0 mm/year, respectively (Perry et al., ).…”
Section: Impacts On Rates and Patterns Of Reef Growth (The Reducing Rmentioning
confidence: 99%
“…3–4 mm/year (Hubbard, ) and a little below this in the Indo‐Pacific region (Dullo, ). Whilst some high coral cover sites may sustain vertical accretion rates sufficient to match near‐future sea‐level rise (van Woesik & Cacciapaglia, ), the critical point is that many contemporary coral reefs are now defined by vertical accretion rates that will be insufficient to keep pace with sea‐level rise. Indeed, recent assessments of reef accretion potential at sites around the tropical western Atlantic and Indian Ocean regions suggest that accretion rates presently average only 1.8 mm/year and 2.0 mm/year, respectively (Perry et al., ).…”
Section: Impacts On Rates and Patterns Of Reef Growth (The Reducing Rmentioning
confidence: 99%
“…Maximum calcium carbonate production under modern‐day climate is approximately 12 kg CaCO 3 m −2 (Edinger et al ), although higher values have been reported (Perry et al , van Woesik and Cacciapaglia ). For the purpose of this model, however, given the spatial resolution of 9.2 km, we assumed that carbonate production was most optimal, in a given locality, i , in the presence of all four species.…”
Section: Methodsmentioning
confidence: 99%
“…Porites lobata and P. rus are generally more tolerant to thermal stress than Acropora species (Loya et al ). To rationalize our approach of selecting four coral species, instead of modeling all of the hundreds of extant coral species, we point to recent studies in Micronesia that found that over 80% of carbonate production of a given reef was contributed by as few as five coral species (van Woesik and Cacciapaglia 2019), and in general less than 10% of the coral species contributed upwards of 75% of the reef's carbonate production (van Woesik and Cacciapaglia ). Furthermore, although dominant coral species differ across reefs, there is considerable functional redundancy in terms of carbonate production, with different dominant species producing similar rates of carbonate production (van Woesik and Cacciapaglia , 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations